PENGARUH BIAYA OPERASIONAL DAN ARUS KAS PENDANAAN TERHADAP PROFITABILITAS PT. CITACONTRAC - Mulia Rahmah, S. Kom., M.Si.; Meliana Meliana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
To determine the effect of operating costs on profitability (Return On Assets), the effect of funding cash flows on profitability (Return On Assets), and the effect of operating costs and funding cash flows on profitability (Return On Assets). The research method used in the research is quantitative descriptive method. The results of this study indicate that operational costs do not affect profitability but have a positive relationship, while funding cash flows do not affect profitability but have a positive relationship. The conclusion of this study is that the increase in profitability cannot be measured in terms of operational costs and cash flow, but also as a whole, including from the performance of the organization. If the organization's performance is satisfactory, the company's profitability will increase, and vice versa will decrease. The suggestion of this research is that the independent variables used should not only be operational costs and cash flow because there are still many factors in the company that can affect profitability such as the management of receivables, debt management, and so forth.